Calibration of a McLeod Gauge (1930)
The McLeod Gauge measures very low pressures of gasses. Its presence in this collection indicates that it was used during the production of Beckman Instruments' early pH meters. These calibrations may have been written by W. E. Baier, Research Manager of the California Fruit Growers' Exchange, as there are other calibrations of the McLeod gauge written by him in the same folder as this document.
Keywords: Pressure gages; Numerical calculations; Scientific apparatus and instruments--Calibration; Scientific apparatus and instruments